2019
DOI: 10.1093/advances/nmz013
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Zinc in Antiviral Immunity

Abstract: Zinc is an essential trace element that is crucial for growth, development, and the maintenance of immune function. Its influence reaches all organs and cell types, representing an integral component of approximately 10% of the human proteome, and encompassing hundreds of key enzymes and transcription factors. Zinc deficiency is strikingly common, affecting up to a quarter of the population in developing countries, but also affecting distinct populations in the developed world as a result of lifestyle, age, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
602
0
27

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 633 publications
(687 citation statements)
references
References 179 publications
13
602
0
27
Order By: Relevance
“…An interesting new finding demonstrated that CQ has characteristics of a zinc ionophore and specifically targets the extracellular trace element zinc to intracellular lysosomes [13]. Zinc is an essential micronutrient, with strictly regulated systemic and intracellular concentrations, and it is physiologically needed for an effective antiviral response [14].…”
Section: Statement Of Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…An interesting new finding demonstrated that CQ has characteristics of a zinc ionophore and specifically targets the extracellular trace element zinc to intracellular lysosomes [13]. Zinc is an essential micronutrient, with strictly regulated systemic and intracellular concentrations, and it is physiologically needed for an effective antiviral response [14].…”
Section: Statement Of Hypothesismentioning
confidence: 99%
“…From in vitro and some clinical studies, it is well known that zinc elicits activity against several viruses [14]. Indeed, it was demonstrated that zinc inhibits the activity of RdRp of Hepatitis E virus [15].…”
Section: Statement Of Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Up to a fifth of the global population is estimated to suffer from different degrees of Zinc deficiency 27 . In the western world, Zinc deficiency is more prevalent among the geriatric population 26 and vegans/vegetarians as well as among people with certain underlying conditions 27 .…”
Section: Hypothesis: Zinc Correction In Sars-cov-2 Patients Improvesmentioning
confidence: 99%
“…Additionally, zinc is associated with antiviral immune response in general, involving various viruses 27 .…”
Section: Zinc Deficiency Hampers Antiviral and Antibacterial Immune Rmentioning
confidence: 99%